An empirical investigation of trust's impact on collective awareness development in virtual teams. (29th December 2006) - Daassi, Mohamed; Jawadi, Nabila; Favier, Marc; Kalika, Michel
This study investigates the relationship between trust and collective awareness levels over time. The study also examines the multi-dimensionality of both trust and collective awareness in virtual teams. Hence, we adopt a longitudinal study to provide a preliminary step towards understanding the dynamic nature of trust and collective awareness in virtual teams. The results of our experiments show that (1) both trust and collective awareness levels increase over time; (2) during the project, task processes are more important than socio-emotional processes; and (3) higher (vs. lower) trust levels are associated with higher (vs. lower) collective awareness levels.